Wolbachia endosymbionts in Drosophila regulate the resistance to Zika virus infection in a sex dependent manner - Tafesh-Edwards, Ghada; Kyza Karavioti, Margarita; Markollari, Klea; Bunnell, Dean; Chtarbanova, Stanislava; Eleftherianos, Ioannis (Frontiers in Microbiology, 2024)
Drosophila melanogaster has been used extensively for dissecting the genetic and functional bases of host innate antiviral immunity and virus-induced pathology. Previous studies have shown that the presence of Wolbachia endosymbionts in D. melanogaster confers resistance to infection by certain viral pathogens. Zika virus is an important vector-borne pathogen that has recently expanded its range due to the wide geographical distribution of the mosquito vector. Here, we describe the effect of Wolbachia on the immune response of D. melanogaster adult flies following Zika virus infection. First, we show that the presence of Wolbachia endosymbionts promotes the longevity of uninfected D. melanogaster wild type adults and increases the survival response of flies following Zika virus injection. We find that the latter effect is more pronounced in females rather than in males. Then, we show that the presence of Wolbachia regulates Zika virus replication during Zika virus infection of female flies. In addition, we demonstrate that the antimicrobial peptide-encoding gene Drosocin and the sole Jun N-terminal kinase-specific MAPK phosphatase Puckered are upregulated in female adult flies, whereas the immune and stress response gene TotM is upregulated in male individuals. Finally, we find that the activity of RNA interference and Toll signaling remain unaffected in Zika virusinfected female and male adults containing Wolbachia compared to flies lacking the endosymbionts. Our results reveal that Wolbachia endosymbionts in D. melanogaster affect innate immune signaling activity in a sex-specific manner, which in turn influences host resistance to Zika virus infection. This information contributes to a better understanding of the complex interrelationship between insects, their endosymbiotic bacteria, and viral infection. Interpreting these processes will help us design more effective approaches for controlling insect vectors of infectious disease.